2020
DOI: 10.1088/1402-4896/ab7fed
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring doping effect in olivine-type NaMnPO4: insights from density functional theory

Abstract: On the basis of spin density functional theory, this paper comparatively investigates the electronic properties of NaMnPO4 doped with As, N and Sb using the generalized gradient approximation (GGA) with the functional parameterized by Perdew–Burke–Ernzerhof correction (PBE). Such doped ions significantly alter the lattice parameters and cell volumes. Density of states (DOS) demonstrates that the dopants introduce impurity states near the edge of the conduction bands. The band gaps are obviously reduced in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Specifically, Na + and Mn 2+ occupy the Mn1 (4a) and Mn2 (4c) positions, respectively, in the olivine structure, while the opposite is true in maricite. Previous theoretical calculations [84] have shown that doping of As, N, and Sb at the P-site in olivinetype NaMnPO 4 reduces the band gap and the ionic character of Na-O bond, thereby achieving a simultaneous increase in electronic and ionic conductivity, with the best effect being achieved by doping Sb. NaMnPO 4 prefers to form an electrochemically inert maricite phase lacking ion diffusion paths under conventional synthesis conditions.…”
Section: Phosphatesmentioning
confidence: 98%
“…Specifically, Na + and Mn 2+ occupy the Mn1 (4a) and Mn2 (4c) positions, respectively, in the olivine structure, while the opposite is true in maricite. Previous theoretical calculations [84] have shown that doping of As, N, and Sb at the P-site in olivinetype NaMnPO 4 reduces the band gap and the ionic character of Na-O bond, thereby achieving a simultaneous increase in electronic and ionic conductivity, with the best effect being achieved by doping Sb. NaMnPO 4 prefers to form an electrochemically inert maricite phase lacking ion diffusion paths under conventional synthesis conditions.…”
Section: Phosphatesmentioning
confidence: 98%
“…As a result, reversible capacities close to 100 mAh g −1 resulted for sodium half-cells in the 2.1-4.5 V interval. Calculations predict that the doping of o-NMP with Sb causes an enhancement in electronic conductivity and Na diffusion, which is of importance in improving the electrochemical performance of o-NMP [92]. The doping approach seems more effective in respect of the storage properties of o-NMP than the classical approach including the carbon coating of o-NMP [91].…”
Section: Maricite and Olivinementioning
confidence: 99%
“…[15][16][17] Numerous investigations have concentrated on the substance NaMnPO 4 , which has appealing properties. [18][19][20][21][22][23][24][25][26][27][28] The literature indicates that the crystalline NaMnPO 4 stabilizes in two types of polymorphs: maricite and olivine. The phosphate group framework is the same in both configurations (space group Pnma).…”
Section: Introductionmentioning
confidence: 99%